Greenhouse Optimization as an Educational and Entrepreneurial Media in Junior High School - Riyadi, Ilham Slamet; Marwendi, Reza Okva; Al-Munip; Saputra, Ahmad Edi (Zabags International Journal of Engagement, 2025)
This study aims to help students can learn science concepts by exploring in any learning sources, for instance through exploring in the greenhouse. Plants in the greenhouse can be integrated contextually in the learning process in order that students can construct their knowledge by correlating the new concepts with their prior knowledge. Furthermore, greenhouse can be optimized as a learning and entrepreneurship media. This training aims to maximize the function of the greenhouse as a learning source and also introduce students about the concepts of entrepreneurship. The activity involves by conducting a workshop of greenhouse utilization and an entrepreneurship training in the use of plants as the products of greenhouse. Through this training, students are expected to be able to aware about greenhouses and creative in producing economic-value products.